A new model of vehicular ad hoc networks based on artificial immune theory. (2018) - Zhou, Yizhe; Peng, Depin
Vehicular ad hoc networks (VANETs) are highly mobile and wireless networks intended to aid vehicular safety and traffic monitoring. To achieve these goals, we propose a VANET model based on immune network theory. Our model outperforms the delay tolerant mobility sensor network (DTMSN) model over a range of node numbers in terms of data packet arrival delay, arrival ratio, and throughput. These findings held true for the on-demand distance vector and connection-based restricted forwarding routing protocols. The model performed satisfactorily on a real road network.